Autologous cord blood transplantation in children with acquired severe aplastic anemia. (9th December 2018) - Sun, Yuan; Liu, Zhouyang; Xiao, Juan; Liu, Xiaomei; Jiang, Fan; Fan, Shifen; Shen, Ying
Abstract: Objective: To investigate the efficacy of ACBT for acquired SAA in children. Methods: Four patients including three girls and one boy were diagnosed with acquired SAA. Their ages were 5, 3, 1, and 3 years, respectively. Patients received an immunoablative preparative regimen using low‐dose antithymocyte globulin, cyclophosphamide, and fludarabine. The unrelated human umbilical cord MSC were infused before the autologous cord blood was transfused on day 0. The first and second patients were not treated with immunosuppressive agents after transplantation. The third and the fourth patients received cyclosporine A for half a year after transplantation followed by a 6‐month taper. Results: Initial hematopoietic reconstitution was seen in all the four patients. There was no association between engraftment time and the number of total cells and CD34+ cells. Relapse was seen in the first case about half a year after the transplantation. The other three patients with durable hematopoietic reconstitution are with good quality of life. No GVHD was observed. Conclusions: Three of four patients maintained prolonged hematopoiesis following an immunosuppressive‐based preparative regimen and infusion of autologous cord blood cells. It is recommended that cyclosporine be maintained for 6 months after transplantation. ACBT could be considered for acquired SAA if available.